GPETAFLR, a biopeptide from Lupinus angustifolius L., protects against oxidative and inflammatory damage in retinal pigment epithelium cells. Issue 11 (24th July 2019) - Millan‐Linares, Maria C.; Toscano, Rocio; Lemus‐Conejo, Ana; Martin, Maria E.; Pedroche, Justo; Millan, Francisco; Montserrat‐de la Paz, Sergio
Abstract: GPETAFLR, an octapeptide released from the enzymatic hydrolysis of lupine ( Lupinus angustifolius L.) protein, has demonstrated anti‐inflammatory effect in myeloid lineage. This work aims to evaluate in retinal pigment epithelium (RPE) cells the protective role of GPETAFLR on both oxidative and inflammatory markers known to be involved in age‐related macular degeneration (AMD). In comparison with stimulated control cells, GPETAFLR increased glutathione production and diminished the secretion and gene expression of VEFG, IL‐1β, IL‐6, IFNγ, and TNF‐α, as well as reactive oxygen species, and nitrite output. Our findings reveal that GPETAFLR, a novel plant peptide, is able to protect against RPE oxidative stress and inflammation. Taken together, these results strongly support innovative nutritional strategies considering Lupinus angustifolius L. as source of proteins to prevent the onset and progression of AMD. Practical applications: We reveal a novel nutraceutical impact of GPETAFLR peptide in human RPE cells to prevent oxidative and inflammatory mediators. Our results support that the intake of Lupine angustifolius L., proposed to be a reservoir of GPETAFLR, could lessen the functional decay of RPE cells, leading therefore to a slowdown of the progress of AMD during age. Not only this work, but also future simple clinical studies should raise new nutritional strategies focused on understanding the etiological role of the foods, nutrition, and metabolism in the pathogenesis of ocular disorders.